PHOSPHIDE SOLID-SOLUTIONS WITHIN THE METAL-RICH PORTION OF THE QUATERNARY SYSTEM CO-FE-NI-P AT 800°C, AND MINERALOGICAL IMPLICATIONS - Drábek M. (My University, 2006)
Solid solutions within the system Co-Fe-Ni-P were studied experimentally at 800 degrees C by means of the evacuated silica tube technique. Three broad sol id-solution series were detected in the system, tetragonal phi, (Co,Ni,Fe)(3)P, hexagonal lambda(1), (Co,Ni,Fe)(2)P, and orthorhombic lambda(2), (Co,Ni,Fe)(2)P. All phosphides known as minerals are situated within these three pseudoternary systems. Cobalt has a remarkable influence on the structure type of (Co,Fe,Ni)(2)P solid solutions, inducing a transition of the hexagonal structure (rich in Fe, Ni) to orthorhombic (rich in Co). Nevertheless, the cobalt content reported in allabogdanite is too low to bring about the transition of the hexagonal lambda(1) structure to the orthorhombic lambda(2) structure. In addition to these solid-solution series, two binary series were detected: a tetragonal one, (Co,Ni)(12)P-5, and over a very narrow field of stability, (Co,Ni)(5)P-2, which is hexagonal. Phosphides with such compositions can be expected in meteorites, in close association with other phosphides.